Measuring value correction and uncertainty analysis for homodyne interferometers - Hausotte, Tino; Percle, Brandon; Manske, Eberhard; Füßl, Roland; Jäger, Gerd (Measurement Science & Technology, 2011)
The Nanopositioning and Nanomeasuring Machine (NMM-1) developed at the Ilmenau University of Technology is equipped with three homodyne plane-mirror miniature interferometers for the measurement of the displacement of a movable corner mirror. The object being measured is placed on the corner mirror, which is positioned by a three-axis drive system. The uncertainty of interferometric length measurements is dependent on several factors. Starting with an improved equation for calculating length, this paper describes a part of the determination of the measurement uncertainty for a displacement measurement using two positions of the measuring mirror. The new approach separates the correlated influencing factors for three positions of the measuring mirror: for the position where the interferometer counter is reset to zero and the other two positions of two measured points. Additionally, the work takes into account the influence of the dead path length and its determination.
Keywords: nanomeasuring; homodyne interferometer; uncertainty; dead path length